2000
DOI: 10.1128/aac.44.3.710-712.2000
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular Mechanisms of Fluoroquinolone Resistance in Pseudomonas aeruginosa Isolates from Cystic Fibrosis Patients

Abstract: Twenty P. aeruginosa isolates were collected from six cystic fibrosis (CF) patients, aged 27 to 33, in 1994 (9 isolates) and 1997 (11 isolates) at the CF Center, Copenhagen, Denmark, and were typed by pulse-field gel electrophoresis (PFGE) or ribotyping. Five of the patients had isolates with the same PFGE or ribotyping patterns in 1997 as in 1994, and ciprofloxacin had a two-to fourfold higher MIC for the isolates collected in 1997 than those from 1994. Genomic DNA was amplified for gyrA, parC, mexR, and nfxB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
66
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 206 publications
(69 citation statements)
references
References 19 publications
1
66
0
2
Order By: Relevance
“…This notion is supported by the low number of natural nfxB mutant strains isolated in clinical settings (21)(22)(23)(24) and is in agreement with the results of the experiments performed by Hirakata et al (10), who showed that an nfxB mutant was less virulent that the parent strain in a mouse model of bacteremia. In contrast, nfxB mutants are highly prevalent among P. aeruginosa isolates from cystic fibrosis patients with chronic respiratory infections (25). Indeed, mutation of nfxB is involved in the early adaptation to the chronic setting (26), perhaps by promoting biofilm growth.…”
mentioning
confidence: 97%
“…This notion is supported by the low number of natural nfxB mutant strains isolated in clinical settings (21)(22)(23)(24) and is in agreement with the results of the experiments performed by Hirakata et al (10), who showed that an nfxB mutant was less virulent that the parent strain in a mouse model of bacteremia. In contrast, nfxB mutants are highly prevalent among P. aeruginosa isolates from cystic fibrosis patients with chronic respiratory infections (25). Indeed, mutation of nfxB is involved in the early adaptation to the chronic setting (26), perhaps by promoting biofilm growth.…”
mentioning
confidence: 97%
“…A variety of substrates can be accommodated by MexCD-OprJ, including antibiotics used in clinics, such as fluoroquinolones, macrolides, and glycylcyclines (9), as well as biocides like triclosan and chlorhexidine, dyes, detergents, and organic solvents (10). Efflux-mediated resistance due to the overexpression of MexCD-OprJ is commonly found in resistant P. aeruginosa isolates from chronic lung infection in cystic fibrosis (CF) patients and occasionally in non-CF patients (11)(12)(13).…”
mentioning
confidence: 99%
“…This phenotype was attributed to (i) reduced intracellular levels of the Pseudomonas quinolone signal (PQS), caused by a shortage of a metabolic precursor (kynurenine or 4-hydroxy-2-heptylquinoline [HHQ]) exported by the pump (17,19), and (ii) MexT acting as a global regulator and indirectly impairing the T3SS in an MexEF-OprN-independent way (18). Information about the rates and traits of nfxC mutants in cystic fibrosis (CF) patients (20,21) and non-CF patients (12,(22)(23)(24) remains scarce. As a plausible explanation, the low virulence of these mutants would be detrimental to their survival in the host or in the hospital setting and would account for their infrequent isolation from clinical samples.…”
mentioning
confidence: 99%